25. Strategies to reduce intertrial variability of motor responses to nerve root and transcranial stimulation: A condition for follow-up studies in the individual patient. Issue 4 (April 2016) - Troni, W.; Di Sapio, A.; Melillo, F.; Malucchi, S.; Bertolotto, A.
Abstract : We investigated the Intertrial Variability and Relative Intertrial Variation (RIV) of latency and area of motor responses to High Voltage Electric Stimulation (HVES) of lumbo-sacral roots and to Transcranial Magnetic Stimulation (TMS) recorded from several sites of lower limbs. The purpose was to obtain normative variability values to detect significant changes in the individual patient in follow up studies. Maximal CMAPs to HVES of lumbo-sacral roots were obtained from 10 proximal and distal muscle districts of lower limbs; MEPs to TMS using the double cone coil were recorded from the same sites. The procedure was repeated twice, 1–2 days apart, in 30 subjects, including healthy volunteers and clinically stable multiple sclerosis patients. The use of stable recording and stimulation sites with maximal root-CMAPs and adequately stabilized MEPs allowed a significant reduction of ITV for all latency and area parameters. Mean RIV values (5th–95th percentile) for Central Motor Conduction Time and Area Ratio (MEP/CMAP) did not exceeded −14.8 and +16.0 ms and −26.0 and +33.7 mV ms, respectively. The combined monitoring of latency and areas indexes allows assessment of both conduction slowing and conduction failure, i.e the variable association of axonal damage and conduction block, which directly correlates with motor impairment.